Antennal morphology and ultrastructure of male and female Ptinus japonicus Reitter, 1877 (Coleoptera: Ptinidae). (3rd April 2019) - Wei, Zhao-Ming; Liu, Hong-Xia; Zhang, Heng; Yao, Fu-Jiao; Qiu, Li-Fei; Tian, Ying-Fang; Lian, Zhen-Min
Abstract: Ptinus japonicus Reitter is a subversive pest of stored-product throughout the world. Scanning electron microscopy (SEM) was used to observe the antennal morphology and sensilla ultrastructure in both sexes of this pest. The antennae of P. japonicus are filiform that comprised scape, pedicel and flagellum with nine flagellomeres. Six types of sensilla were identified, including Böhm sensilla (Bs), two subtypes of sensilla basiconica (SbI-II), sensilla styloconica (Sst), four subtypes of sensilla chaetica (SchI-IV), sensilla coeloconica (Sco), two subtypes of sensilla trichodea (St I-II). The antennae of Ptinus japonicus exhibit obvious sexual dimorphism in antennal size, the type and size of the sensilla, the distribution and abundance of the sensilla. The length of antennae in males was significantly longer than these in females. Sensilla trichodea I (StI) were found only in males. The number of sensilla basiconica (Sb) and Sensilla chaetica IV (SchIV) in females were higher than in males. Bs in females was longer than in males. The results of this study provide theoretical basis and material for the further study on mating and habitant searching, and may provide a new sight into semiochemical-based control of spider beetles.